Rekayasa Sosial Sistem Integritas Penyelenggara Pemilu - Ida Budhiati (Jurnal Hukum Sasana, 2022)
This article elaborates the dynamics of paradigm-shift in election law through the lense of Roscoe Pound's concept of “law as a tool of social engineering”. This article argues that that the nature of election should not be reduced to its formal duties, but instead expanding its role as a means to promote credibility and integrity of Indonesian democracy. For such role, this article analyzed the transformation of Indonesian election system as part of social engineering in ensuring the integrity of process and result of the election, as well as the integrity of the election holders. The most notable feature of this transformation is the establishment of Election Holder Board of Ethics (DKPP) as regulated in Election Holder Law 15/2011 and maintained in Election Law 7/2017. This special feature of Indonesia’s election holder ethical court system will be highlighted and discussed within the article.